Colombian experience in the treatment of hepatitis c with direct-acting antiviral agents (2019)
There are few published real-world studies on hepatitis C in Latin America. This paper describes a cohort of Colombian subjects treated with direct-acting antiviral agents. A total of 195 patients from 5 hepatology centers in 4 Colombian cities were retrospectively studied. For each patient, serum biomarkers were obtained, and Child-Pugh, MELD, cirrhosis and fibrosis stage were calculated. Additionally, viral load was quantified at initiation, end of treatment and at 12 weeks of completion. Adverse effects were recorded. Patients with liver transplant were compared with non-transplanted patients in terms of serum biomarkers. The patients had received 9 different regimes. The most prevalent viral genotype was 1b (81.5%). Overall, 186 patients (95.4%) attained sustained virologic response. When comparing transplanted vs. non-transplanted patients, those in the non-transplanted group were more likely to have cirrhosis (52.6% vs. 12.5%, p = 0.0004). Pre-treatment viral load was higher in the transplant group (1 743 575 IQR = 1 038 062-4 252 719 vs. 345 769 IQR = 125 806-842 239; p less than 0.0001) as well as ALT and AST levels (82.5 IQR 43.5-115.5 vs. 37.0 IQR = 24.7-73.3; p = 0.0009 and 70 IQR = 41-140 vs. 37 IQR = 24-68; p = 0.004 respectively). Adverse events were reported by 28.7% of the patients; asthenia (5.6%) was the most prevalent. Our results are comparable with those from other countries in terms of therapy and biomarkers. However, our cohort reported less adverse events. Further research is needed in the region. © 2019, Instituto de Investigaciones Medicas. All rights reserved.